THE REFORM OF THE COMMON FISHERIES POLICY AND THE ROLE OF INDIVIDUAL TRANSFERABLE QUOTAS IN THE CONSERVATION AND MANAGEMENT REGIME - Lopes, Rui (2012)
Overcapacity and overcapitalisation of the fishing sector have been identified as the principal failure of the Common Fisheries Policy (CFP). This conclusion may be well important in the CFP Reform, 2012, and put again the discussion about the tools that can be used to get sustainable management and better cohesion. The main purpose of this paper is to enter this debate, making the repertory of the maintained guidelines and of the fundamental changes that are introduced in this new reform, and discussing and evaluating their relevance and potentialities, as well as their difficulties and risk factors. A special attention is given to the possibility of introducing a more focused approach on Rights Based Management in the conservation and management of resources regime. The feasibility of introducing ITQs (Individual Transferable Quotas) in the context of European fisheries is discussed.